Muslims of Hyderabad - Vithal, B.P.R. (2002)
When the state of Hyderabad was trifurcated, the Muslims of the Marathwada region joined the Bombay state, where they counted for little. The Muslims of the Karnataka region had to contend with the sophisticated Muslims elite of Bangalore. On the other hand, the Muslims of Hyderabad remained in Hyderabad, the seat of their previous rule and culture. They however remained concentrated in the Old City in a ghetto environment and complex. Their strength in the capital city, and marginal significance elsewhere in the state, made them convenient pawns in the games politicians played. As a result a Muslim leadership arose whose concern was that they alone should be able to move this pawn. Meanwhile, a Cyberabad, based on English, was being developed for modern young persons. Young Muslim boys and girls of the Old City were eager to have English education so that they could get good jobs. The wheel had come full circle. The Muslims of the old city had to choose once again between pride in their history and hopes for their future. - Reproduced.
Keywords: Muslims - India - Andhra Pradesh; Muslims - India; Muslims